Convulsion and Respiratory Depression After Interscalene Brachial Plexus Block with 0.5 % Ropivacaine (Case Report) (Annals of Medical Research, 2021)
None
Keywords: Regional anesthesia, Brachial plexus block, Ropivacaine, Convulsion, Respiratory depression